2017
DOI: 10.5964/jnc.v3i2.46
|View full text |Cite
|
Sign up to set email alerts
|

How and why do number-space associations co-vary in implicit and explicit magnitude processing tasks?

Abstract: Evidence for number-space associations in implicit and explicit magnitude processing tasks comes from the parity and magnitude SNARC effect respectively. Different spatial accounts were suggested to underlie these spatial-numerical associations (SNAs) with some inconsistencies in the literature. To determine whether the parity and magnitude SNAs arise from a single predominant account or taskdependent coding mechanisms, we adopted an individual differences approach to study their correlation and the extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 70 publications
6
24
0
Order By: Relevance
“…The relationship between the slope distributions of the different tasks were further investigated with Pearson's correlation coefficient (Table 3 and Figure 3). In line with previous studies (ρ = 0.08 in Georges, Hoffmann, & Schiltz, 2017 and ρ = 0.2 in Georges, Hoffmann, & Schiltz, 2018), the magnitude classification and the parity judgement tasks did not correlate. The only significant positive correlation emerged between the magnitude classification and phoneme detection tasks.…”
Section: Slopessupporting
confidence: 89%
“…The relationship between the slope distributions of the different tasks were further investigated with Pearson's correlation coefficient (Table 3 and Figure 3). In line with previous studies (ρ = 0.08 in Georges, Hoffmann, & Schiltz, 2017 and ρ = 0.2 in Georges, Hoffmann, & Schiltz, 2018), the magnitude classification and the parity judgement tasks did not correlate. The only significant positive correlation emerged between the magnitude classification and phoneme detection tasks.…”
Section: Slopessupporting
confidence: 89%
“…1, respectively, for unstandardized slopes). However, in some in-lab studies reliabilities have been comparable to those from the online study (e.g., .55 in Georges et al, 2017).…”
Section: Reliability Of the Effectsmentioning
confidence: 86%
“…Although many studies on interindividual differences in the SNARC have been conducted, the studies on those differences were frequently not replicated, in line with current general concerns about reproducibility in psychology (in line with current general concerns about reproducibility in psychology; e.g., Open Science Collaboration, 2015), or were largely inconclusive. Possible reasons include that the reported correlations or between-group differences have mostly been small to moderate (in most cases between .25 to .44; e.g., Hoffmann, Pigat, & Schiltz, 2014b); in several instances, the reliability of the SNARC was relatively low (e.g., Georges, Hoffmann, & Schiltz, 2017); and the tested samples have been relatively small (yielding insufficient power). Namely, the sample sizes in published SNARC studies typically have not exceeded 100 participants.…”
Section: The Snarc Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, a stronger effect of mental rotation (i.e., larger increase in the time to decide on object identity depending on the degree to which it is rotated) relates to more pronounced SNARC (Viarouge, Hubbard, & McCandliss, 2014). In a more recent study it was shown that an individual's visualization profile moderates the relationship between magnitude and parity SNARC (Georges, Hoffmann, & Schiltz, 2017a). Importantly, visuospatial skills themselves are also correlated with different types of math skill at several stages of development (Mix et al, 2016).…”
Section: Variation In Visuo-spatial Skills Operationalizationmentioning
confidence: 99%